Characterization of hydraulical parameters in paleogenic fluvial deposits in the Volta Redonda Basin, R J - Barboza, Ana Carolina Lisbôa (Universidade Federal do Rio de Janeiro, 2007)
The present study aims for the characterization of the hydrogeological parameters of the Paleogenic fluvial deposits of Volta Redonda Geological Basin, through hydraulic conductivity determinations and grain sized analyses. The overall goal was to produce a hydrogeological data base applicable to the characterization of hydrofacies (interconnected sedimentary bodies with distinct hydraulic properties) and the modeling groundwater flow. The used methods used consisted of in situ permeability determinations (Guelph permeameters) and laboratory tests (variable head permeameter), besides grain size analyses carried out in each sedimentary facies in the study area. These sedimentary facies were characterized by Marques (2006) and belong to the Resende and Pinheiral formations. The permeameter results were coherent to the sedimentological characteristics. The Resende Formation sedimentary deposits are constituted by medium to fine sand with presence of argillaceous matrix and present moderate to very low hydraulic conductivity, varying between 10-4 to 10-8 cm/s, which indicates a poor reservoir. The Pinheiral Formation presents sandy layers with conglomeratic lenses, limited by small thickness pelitic intervals, with a very low permeability, with a hydraulic conductivity varying between 10-5 to 10-7 cm/s. The upper layer has the maximum permeability, around 10-3 cm/s. This formation presents a medium reservoir characteristics and it must be taken into consideration that the upper layer has as role in recharge to the aquifer. From the results of hydraulic conductivity, that varies from 10-8 to 10-3 cm/s for the Resende and Pinheiral formations, it is concluded that these deposits a low to medium hydraulic conductivity, explaining the low productivity of the water-bearing multilayered aquifer of Volta Redonda Basin.